2017
DOI: 10.1097/mco.0000000000000369
|View full text |Cite
|
Sign up to set email alerts
|

Timing of the initiation of parenteral nutrition in critically ill children

Abstract: Purpose of Review To review the current literature evaluating clinical outcomes of early and delayed parenteral nutrition initiation among critically ill children. Recent Findings Nutritional management remains an important aspect of care among the critically ill, with enteral nutrition (EN) generally preferred. However, inability to advance enteral feeds to caloric goals and contraindications to EN often leads to reliance on parenteral nutrition (PN). The timing of PN initiation is varied among critically i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 22 publications
0
17
0
1
Order By: Relevance
“…In extreme cases like sepsis, blockage of lipid oxidation and catabolism of amino acid deteriorate the homeostasis and eventually lead to poor prognosis or death 15,26 . Therefore, decreased gluconeogenesis from amino acid and utilization of lipid in the present study suggested the TPN support may help the metabolic transition to homeostasis and thus enhance the patients’ recovery 25,28 .…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…In extreme cases like sepsis, blockage of lipid oxidation and catabolism of amino acid deteriorate the homeostasis and eventually lead to poor prognosis or death 15,26 . Therefore, decreased gluconeogenesis from amino acid and utilization of lipid in the present study suggested the TPN support may help the metabolic transition to homeostasis and thus enhance the patients’ recovery 25,28 .…”
Section: Discussionmentioning
confidence: 60%
“…Total parenteral nutrition (TPN) provides nutrients of amino acids, lipids, and vitamins, which may provide additional benefits for the transition of metabolism and help the body be tolerant of following EN 5,7 , while the risk of blood glucose disorder or infection are significant concerns for TPN application 7,28 . In the present study, though the sample size is relatively small, clinical outcomes between the two groups indicated no increased infection or other complications.…”
Section: Discussionmentioning
confidence: 99%
“…These recommendations acknowledge the study results to begin PN after seven days, but counter with expert opinion the option to begin PN 24 hours after PICU admission. Thus, current guideline recommendations lack focused specificity for standard provision of care regarding PN initiation 7. The broad national debate over appropriate PN initiation, reflects the range of opinions expressed at our facility during our initial consensus discussions.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there were several aspects of the study design that limit external validity . In the absence of data, a reasonable approach in infants and children receiving ECMO may be to emphasize early and cautious advancement of EN and to initiate PN within 3–5 days in children with malnutrition and within 5–7 days in well‐nourished children if nutrient delivery goal has not been achieved by EN alone …”
Section: Timing and Route Of Nutrient Deliverymentioning
confidence: 99%